[PP.LB02.10] 60-DAY ALCL3 EXPOSURE AT HUMAN DIETARY LEVELS INCREASES VASCULAR REACTIVITY IN CONDUCTANCE AND RESISTANCE ARTERIES IN RATS. (September 2016) - Martinez, C.; Escobar, A.; Piagette, J.; Vassallo, D.; Alonso, M.J.; Salaices, M.; Peçanha, F.; Miguel, M.; Wiggers, G.
Abstract : Objective: To investigate the effects of a 60-day aluminum (Al) exposure at doses similar to human dietary levels on cardiovascular system. Design and method: 20 three-month-old male Wistar rats ( ± 300 g) were divided into two groups and received for 60 days in drinking water: a) Control - ultrapure water; b) AlCl3 - aluminum chloride at a dose of 8.3 mg/kg bw. Systolic blood pressure (SBP) was measured by plethysmography. Vascular function was studied in aortic and mesenteric resistance arteries (MRA) in isolated organ bath (J Pharmacol Exp Ther 321: 381–388, 2007 and Circ Res 41:19–26, 1977). Concentration-response curves to acetylcholine (ACh) and sodium nitroprusside were performed. Vasoconstrictor response to phenylephrine (PHE) in presence and absence of endothelium and in presence of NOS inhibitor (L-NAME), potassium channels blocker (TEA), NAD (P)H oxidase inhibitor (apocynin), superoxide dismutase (SOD), non-selective COX inhibitor (indomethacin), selective COX-2 inhibitor (NS 398), and AT1 selective receptor blocker (losartan), were analyzed. Systemic and vascular reactive oxygen species (ROS), lipid peroxidation and total antioxidant capacity, were measured. Results were expressed as mean and SEM, compared by t–test and ANOVA followed by Bonferroni test ( * P < 0.05). Ethics Committee Approval 028/2014 - Unipampa. Results: AlCl3-exposure at low doses increased SBP (Ct: 120.3 ± 1.17 vs Al:126.9 ± 1 * mmHg, n = 8), decreased ACh induced concentration-dependent relaxation, increased vasoconstrictor response to PHE (MRA - Rmax % to KCl Ct: 111.7 ± 5.4 % vs AlCl3: 126.1 ± 11.4 %*, Aorta - Ct: 89.7 ± 17.4 % vs AlCl3: 111 ± 22.4 %* n = 10), decreased the endothelium vasoconstrictor – modulation, nitric oxide (NO) bioavailability, potassium channels involvement, as well as increased ROS production from NAD (P)H oxidase and contractile prostanoids mainly from COX-2. Al exposure at low levels increased plasmatic and vascular ROS production and lipid peroxidation as well as altered the antioxidant status in plasma, aorta and MRA. Conclusions: Our results demonstrate that 60-day chronic exposure to low doses of AlCl3, which reflect common human dietary Al intake induces endothelial dysfunction probably as a result of the decreased NO bioavailability induced by increases on oxidative stress.